Platinum-Induced Peripheral Neuropathy (PIPN): ROS-Related Mechanism, Therapeutic Agents, and Nanosystems - Hu, Xi; Jiang, Zhijie; Teng, Longyu; Yang, Hongyu; Hong, Dongsheng; Zheng, Dongsheng; Zhao, Qingwei (Frontiers in Molecular Biosciences, 2021)
Platinum (Pt) drugs (e.g., oxaliplatin, cisplatin) are applied in clinic worldwide for the treatment of various cancers. However, Pt-induced peripheral neuropathy (PIPN) caused by the accumulation of Pt in the peripheral nervous system limits the clinical application, whose prevention and treatment are still a huge challenge. To date, Pt-induced reactive oxygen species (ROS) generation has been studied as one of the primary mechanisms of PIPN, whose downregulation would be feasible to relieve PIPN. This review will discuss ROS-related PIPN mechanisms including Pt accumulation in dorsal root ganglia (DRG), ROS generation and cellular regulation. Based on them, some antioxidant therapeutic drugs will be in detail summarized to alleviate the Pt-induced ROS overproduction. More importantly, we focus on the cutting-edge nanotechnology in view of ROS-related PIPN mechanisms, and will discuss the rational fabrication of tailor-made nanosystems for efficiently preventing and treating PIPN. Lastly, the future prospects and potential breakthroughs of these anti-ROS agents and nanosystems will be briefly discussed.